Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Green synthesis of glycerol carbonate from glycerol and CO2 using a polymeric ionic liquid catalyst: An experimental and theoretical study - Yi-Lin Lee; Yu-Chi Kao; He-Xiang Xu; Shun Tsunekawa; Masaaki Yoshida; Yi-Pei Li; Chechia Hu (Journal of Cleaner Production, 2026)

A novel approach for utilizing UAV imaging and deep learning techniques for river channel measurement and flood simulation - Jen-Yu Han; Chun-Jia Huang; Yuan-Shun Chang; Yen-Cheng Lin; Hao-Che Ho (Geomorphology, 2026)

Utilizing conjugation effect of nitrogen unshared electron to architect redox-active polymer for sodium-ion storage - Liang-Yu Wang; Shun-Yu Yao; Jing-Zhe Wan; Qi-Hang Wang; Chao Ma; Jiu-Lin Wang; Kai-Xue Wang (Chemical Engineering Journal, 2026)

Bacteriophage Cocktail in Hydrogel Dressing Modulates Macrophage Responses and Induces Skin Cell Migration - Ming-Shun Wu; Sheng-Jie Shiue; Qiu-Yun Zheng; Yu-Sheng Chen; Hsin-Yi Lin (Tissue Engineering and Regenerative Medicine, 2026)

Nobiletin alleviates heat stress-induced meiotic arrest via restoring CDK1 and MAPK activity in porcine oocytes - Jae-Min Sim; Song-Hee Lee; Cheng-Lin Zhan; Qin-Yue Lu; Gyu-Hyun Lee; Hyeon-Ji Song; Yu-Jin Jo; Ji-Su Kim; Eui-Bae Jeung; Xiang-Shun Cui (Theriogenology, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Integrating structural equation modeling and machine learning to unravel the drivers of fine-grained urban thermal patterns - Ying Ding; Chen Huang; Jue-Yu Lin; De-Shun Xu; Yang-Zi Che; Ying Sun; Wei-Lin Liao (Urban Climate, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

Nutrient recovery from high-salinity dairy wastewater through the cultivation of acclimatized microalgae - Rui Xiao; Erika Carter; Austin Allen; Pei-Lin Tan; Yu-Hua Zheng; Qian Chen; Shun-Ni Zhu; Sudeep C. Popat; Allan Knopf; Clinton F. Williams; Howard H. Chou; Huan Chen (Journal of Water Process Engineering, 2025)

Cis-regulation of the CYP6CS1 gene and its role in mediating cross-resistance in a pymetrozine-resistant strain of Nilaparvata lugens - Pin-Xuan Lin; Yu-Xuan Peng; Ji-Yang Xing; Zhao-Yu Liu; Fang-Rui Guo; Joshua A. Thia; Cong-Fen Gao; Shun-Fan Wu (Insect Biochemistry and Molecular Biology, 2025)

Specific nickel recovery using screen-printed carbon electrode electrografted with ionic liquid - Chun-Hao Tai; Shih-Hao Lin; Meng-Shun Huang; Hsiang-Yu Wang (Environmental Pollution, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Functional characterization of four antenna-enriched odorant binding proteins in Rhaphuma horsfieldi reveals the importance of RhorOBP1 in odorant recognition and insecticide resistance - Yin-Lan Liang; Shun-Si Li; Ning-Na Yin; Shu-Lin Li; Yu-Yue Lu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2024)

Evaluating long-term reductions in trace metal emissions from shipping in Shanghai - Meng Wang; Yusen Duan; Juntao Huo; Jia Chen; Yanfen Lin; Qingyan Fu; Tao Wang; Yu Huang; Junji Cao; Shun-cheng Lee (Journal of Hazardous Materials, 2024)

Toxicity, mutagenicity, and source identification of polycyclic aromatic hydrocarbons in ambient atmosphere and flue gas - Shih Yu Pan; Ya Syuan Wu; Yu-Cheng Chen; Yen-Shun Hsu; Yu Chi Lin; Pao Chen Hung; Charles C.-K. Chou; Somporn Chantara; Yuan Cheng Hsu; Kai Hsien Chi (Environmental Science and Pollution Research, 2024)
This study aimed to assess the characteristics of particulate matter (PM) and polycyclic aromatic hydrocarbons (PAHs) from various stationary and mobile emission sources in Taiwan, with a focus on source apportionment and associated health risks. The northern power plant, equipped with bag filters operating at 150 °C, had significantly lower FPM and CPM levels (0.44 and 0.13 mg/m 3 , respectively) compared to the central and southern power plants, which used electrostatic precipitators operating at 250 °C (FPM, 1.45–8.35 mg/m 3 ; CPM, 2.37–3.73 mg/m 3 ). Additionally, emissions from diesel vehicles under both idle and high-speed conditions exhibited higher FPM levels (3.46–4.67 mg/m 3 ) than gasoline vehicles (0.19–0.40 mg/m 3 ). In terms of PAH toxicity, diesel vehicle emissions had significantly higher BaP-TEQ (87.3 ng/m 3 ) and BaP-MEQ (25.9 ng/m 3 ) levels compared to power plants (BaP-TEQ, 5.49 ng/m 3 ; BaP-MEQ, 2.65 ng/m 3 ). The highest ambient concentrations of PM2.5, BaP-TEQ, and BaP-MEQ were recorded at traffic sites, with values of 48 ± 36 µg/m 3 , 0.29 ng/m 3 , and 0.11 ng/m 3 , respectively. Differences in PAH distributions between stationary and mobile sources were influenced by factors such as pollution control technologies, combustion temperatures, and fuel types. Diesel vehicle emissions were dominated by benzo[g,h,i]perylene (BghiP), indeno[1,2,3-cd]pyrene (IND), benzo[a]pyrene (BaP), and benzo[b]fluoranthene (BbF) under idle conditions, while phenanthrene (PA), pyrene (Pyr), and BghiP were prevalent under high-speed conditions. Source apportionment conducted using principal component analysis (PCA) and positive matrix factorization (PMF) identified diesel and gasoline vehicles as the dominant contributors to atmospheric PAHs in Taiwan, accounting for 38% of the total, followed by coal-fired power plants at 35%. The highest lifetime excess cancer risk (ECR) of 2.5 × 10⁻ 5 was observed in traffic-dense areas, emphasizing the public health implications of vehicle emissions. The study adds credibility to the source apportionment findings, and the health risk analysis highlights variations across different regions, including traffic, urban, rural, and background zones.

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

An unsaturated chain carbonate additive contributing to high-performance LiFePO4//graphite battery at broad temperature range - Xin-Lin Zhang; Bin Dong; Yi Jin; Jia-Shun Song; Li Li; Jia-Yu Wang; Yu-Ying Zhu; Yan-Yun Sun (Chemical Engineering Journal, 2024)

Environmental explanation of prostate cancer progression based on the comprehensive analysis of polychlorinated biphenyls - Wen-Cai Zheng; Fei Lin; Qian-Ren-Shun Qiu; Yu-Peng Wu; Zhi-Bin Ke; Shao-Hao Chen; Dong-Ning Chen; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Science of The Total Environment, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Buried interface modification and light outcoupling strategy for efficient blue perovskite light-emitting diodes - Shuxin Wang; Zhiqiu Yu; Jiajun Qin; Guoyi Chen; Yongjie Liu; Shuaiwei Fan; Chao Ma; Fang Yao; Hongsen Cui; Shun Zhou; Kailian Dong; Qianqian Lin; et al. (Science Bulletin, 2024)

Comparative analysis of Deinagkistrodon acutus venom from Taiwan and China utilizing chromatographic, electrophoretic, and bioinformatic approaches, along with ELISA employing a monospecific antivenom - Tein-Shun Tsai; Inn-Ho Tsai; Jing-Lin Qiu; Yuen-Ying Chan; Yu-Wei Chiang (Toxicon, 2024)

Roles of changes in land weathering intensity in the Nd cycle of the South China Sea during the past 30 kyr as inferred from neodymium isotopic composition in foraminifera - Yi Huang; Christophe Colin; Zhifei Liu; Bertaz Joffrey; Arnaud Dapoigny; Eric Douville; Zhaojie Yu; Andrew Tien-Shun Lin (Chemical Geology, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Reverse genetic study reveals the molecular targets of chordotonal organ TRPV channel modulators - Yu-Xuan Peng; Zhao-Yu Liu; Pin-Xuan Lin; Shao-Cong Su; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2023)

Detection of micro-plasma-induced exosomes secretion in a fibroblast-melanoma co-culture model - Han Lee; Jiunn-Der Liao; Tak-Wah Wong; Che-Wei Wu; Bo-Yao Huang; Shun-Cheng Wu; Pei-Lin Shao; Yu-Han Wei; Ming-Hsien Cheng (Analytica Chimica Acta, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Plasma-activated silicon–glass high-strength multistep bonding for low-temperature vacuum packaging - Mingzhi Yu; Libo Zhao; Yongliang Wang; Yong Xia; Yintao Ma; Yanbin Wang; Xiangguang Han; Yao Chen; Shun Lu; Guoxi Luo; Nan Zhu; Ping Yang; et al. (Chemical Engineering Journal, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Exogenous Methylglyoxal Ameliorates Source Strength and Retrieves Yield Loss Under Drought Stress During Grain Filling in Maize - Yi-Hsuan Lin; Yu-Ka Jin; Zhen-Yuan Chen; Zu-Dong Xiao; Si Shen; Shun-Li Zhou (Journal of Plant Growth Regulation, 2023)

Genomic architecture underlying morphological and physiological adaptation to high elevation in a songbird - Chia‐Wei Lu; Shih‐Ting Huang; Shun‐Jen Cheng; Chen‐Tau Lin; Yu‐Cheng Hsu; Cheng‐Te Yao; Feng Dong; Chih‐Ming Hung; Hao‐Chih Kuo (Molecular Ecology, 2023)
Organisms often acquire physiological and morphological modifications to conquer ecological challenges when colonizing new environments which lead to their adaptive evolution. However, deciphering the genomic mechanism of ecological adaptation is difficult because ecological environments are often too complex for straightforward interpretation. Thus, we examined the adaptation of a widespread songbird—the rufous‐capped babbler ( Cyanoderma ruficeps )—to a relatively simple system: distinct environments across elevational gradients on the mountainous island of Taiwan. We focused on the genomic sequences of 43 birds from five populations to show that the Taiwan group split from its sister group in mainland China around 1–2 million years ago (Ma) and colonized the montane habitats of Taiwan at least twice around 0.03–0.22 Ma. The montane and lowland Taiwan populations diverged with gene flow between them, suggesting strong selection associated with different elevations. We found that the montane babblers had smaller beaks than the lowland ones, consistent with Allen's rule, and identified candidate genes— COL9A1 and SOX11 —underlying the beak size changes. We also found that altitudinally divergent mutations were mostly located in noncoding regions and tended to accumulate in chromosomal inversions and autosomes. The altitudinally divergent mutations might regulate genes related to haematopoietic, metabolic, immune, auditory and vision functions, as well as cerebrum morphology and plumage development. The results reveal the genomic bases of morphological and physiological adaptation in this species to the low temperature, hypoxia and high UV light environment at high elevation. These findings improve our understanding of how ecological adaptation drives population divergence from the perspective of genomic architecture.

Confinement mechanism of FRP-confined concrete-encased cross-shaped steel columns - Le Huang; Tao Yu; Guan Lin; Shi-Shun Zhang (Engineering Structures, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Experimental study on the distribution law of the blade foot resistance of a large deep-water open caisson in sand - Bing-nan Jiang; Ting Yu; Wen-ming Peng; Ying-bin Zhang; Shun-bin He; Jian-lin Ma (Ocean Engineering, 2023)

Multifunctional lysosome-targetable fluorescent probe for imaging peroxynitrite in acute liver injury model - Kai Wang; Rui Guo; Xu-Yang Chen; Yu-Shun Yang; Lu-Qin Qiao; Ming-Lin Wang (Chemical Engineering Journal, 2023)

Defect inspection of indoor components in buildings using deep learning object detection and augmented reality - Shun-Hsiang Hsu; Ho-Tin Hung; Yu-Qi Lin; Chia-Ming Chang (Earthquake Engineering and Engineering Vibration, 2023)

RsmA3 modulates RpoS through the RetS‐Gac‐Rsm signalling pathway in response to H 2 O 2 stress in the phytopathogen Pseudomonas syringae - Xun Yu; Cui Meng; Xiaocheng Tan; Yuwei Su; Zhiping Cao; Tzann‐Shun Hwang; Lin Li (Environmental Microbiology, 2022)
Reactive oxygen species are a fatal challenge to the plant pathogenic bacterium Pseudomonas syringae . In this study, we reveal that the global regulatory protein RsmA3 from the RetS‐Gac/Rsm signalling pathway modulates RpoS in the early‐log growth phase in the P . syringae wild‐type strain MB03, thereby regulating oxidative tolerance to H 2 O 2 and ultimately affecting pathogenicity to the host plant. Following increased H 2 O 2 by external addition or endogenous induction by menadione, the resistance of the mutant strain Δ retS to H 2 O 2 is significantly enhanced due to rapid increases in the transcription of Rsm‐related non‐coding small RNAs (nc sRNAs), a sigma factor RpoS, and H 2 O 2 ‐detoxifying enzymes. Moreover, the Δ retS mutant is significantly less pathogenic in cucumber leaves. Seven Rsm‐related nc sRNAs (namely, rsmZ , rsmY and rsmX 1–5 ) show functional redundancy in the RetS‐Gac‐Rsm signalling pathway. External addition of H 2 O 2 stimulates increases in the transcription of both rsmY and rsmZ . Thus, we propose a regulatory model of the RetS‐Gac‐Rsm signalling pathway in P . syringae MB03 for the regulation of H 2 O 2 tolerance and phytopathogenicity in the host plant.

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Roles of FERONIA-like receptor genes in regulating grain size and quality in rice - Long Wang; Dandan Wang; Zhuhong Yang; Shun Jiang; Jianing Qu; Wei He; Zhenming Liu; Junjie Xing; Youchu Ma; Qinlu Lin; Feng Yu (Science China Life Sciences, 2021)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Matriptase and prostasin proteolytic activities are differentially regulated in normal and wounded skin - Shun-Cheng Chang; Chien-Ping Chiang; Chih-Hsin Lai; Po-Wen A. Du; Yu-Sin Hung; Yu-Hsuan Chen; Hui-Yu Yang; Hao-Yu Fang; Shiao-Pieng Lee; Hung-Jen Tang; Jehng-Kang Wang; Michael D. Johnson; et al. (Human Cell, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Pathological and therapeutic aspects of matrix metalloproteinases: implications in childhood leukemia - Yi-Hsuan Hsiao; Shih-Chi Su; Chiao-Wen Lin; Yu-Hua Chao; Wei-En Yang; Shun-Fa Yang (Cancer and Metastasis Reviews, 2019)

Algicoccus marinus gen. nov. sp. nov., a marine bacterium isolated from the surface of brown seaweed Laminaria japonica - Jun-Jie Ying; Shun-Li Zhang; Chao-Yu Huang; Lin Xu; Zhe Zhao; Min Wu; Cong Sun (Archives of Microbiology, 2019)

Antagonism of Ca2+-sensing receptors by NPS 2143 is transiently masked by p38 activation in mouse brain bEND.3 endothelial cells - Cing-Yu Chen; Mann-Jen Hour; Wen-Chuan Lin; Kar-Lok Wong; Lian-Ru Shiao; Ka-Shun Cheng; Paul Chan; Yuk-Man Leung (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Deformation process and mechanism analyses for a planar sliding in the Mayanpo massive bedding rock slope at the Xiangjiaba Hydropower Station - Shi-lin Zhang; Zhao-hui Zhu; Shun-chao Qi; Yu-xiang Hu; Qing Du; Jia-wen Zhou (Landslides, 2018)

Localization of Maize Critical N Curve and Estimation of NNI by Chlorophyll - Xiao-Gui Liang; Zuo-Lin Zhang; Li-Li Zhou; Si Shen; Zhen Gao; Li Zhang; Shan Lin; Yu-Qiang Pan; Shun-Li Zhou (International Journal of Plant Production, 2018)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Physiological and proteomic analysis in two wild tomato lines under waterlogging and high temperature stress - Hsin-Hung Lin; Kuan-Hung Lin; Jia-Yu Syu; Shun-Yuan Tang; Hsiao-Feng Lo (Journal of Plant Biochemistry and Biotechnology, 2016)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Association of IL-18 promoter gene polymorphisms with rheumatoid arthritis: a meta-analysis - Li-Ping Cai; Li-Juan Zhou; Shun-Yu Lu; Ying-E Liang; Xiao-Ying Chen; Lin Liu; Jun Lin (Molecular Biology Reports, 2014)

Suppression of PI3K/Akt signaling by synthetic bichalcone analog TSWU-CD4 induces ER stress- and Bax/Bak-mediated apoptosis of cancer cells - Meng-Liang Lin; Shih-Shun Chen; Ren-Yu Huang; Yao-Cheng Lu; Yu-Ren Liao; Mopuru Vijaya Bhaskar Reddy; Chuan-Chun Lee; Tian-Shung Wu (Apoptosis, 2014)

ROCK inhibition prevents early mouse embryo development - Xing Duan; Kun-Lin Chen; Yu Zhang; Xiang-Shun Cui; Nam-Hyung Kim; Shao-Chen Sun (Histochemistry and Cell Biology, 2014)

Canyon-infilling and gas hydrate occurrences in the frontal fold of the offshore accretionary wedge off southern Taiwan - Che-Chuan Lin; Andrew Tien-Shun Lin; Char-Shine Liu; Chorng-Shern Horng; Guan-Yu Chen; Yunshuen Wang (Marine Geophysical Research, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Effects of isoflurane exposure during pregnancy on postnatal memory and learning in offspring rats - Fei-juan Kong; Yu-wen Tang; Ai-fei Lou; Hong Chen; Lin-hao Xu; Xiao-ming Zhang; Hui-shun Lu (Molecular Biology Reports, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Analysis of the mechanisms underlying the endothelium-dependent antivasoconstriction of puerarin in rat aorta - Li-Ping Yan; Yu-Lan Zhuang; Shun-Wan Chan; Shi-Lin Chen; Gang-Gang Shi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Coenzyme Q10 protect against ischemia/reperfusion induced biochemical and functional changes in rabbit urinary bladder - Yung-Shun Juan; Tasmina Hydery; Anita Mannikarottu; Barry Kogan; Catherine Schuler; Robert E. Leggett; Wei-Yu Lin; Chun-Hsiung Huang; Robert M. Levin (Molecular and Cellular Biochemistry, 2008)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)